Results of a German nationwide survey on perioperative cardiac management in vascular surgery - Dovzhanskiy, Dmitriy I.; Bischoff, Moritz; Passek, Karola; Böckler, Dittmar (Langenbeck's archives of surgery, 2024)
Because of the lack of specific recommendations concerning cardiac risk stratification before vascular surgery, appropriate decisions remain individual. The aim of the present study was to evaluate the perioperative cardiac management in vascular surgery in Germany.
Online eröffentlicht: 12. November 2024
Gesehen am 15.05.2025